1987
DOI: 10.1084/jem.165.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-defective, genetically susceptible CBA/N mice have an altered Salmonella typhimurium-specific B cell repertoire.

Abstract: CBA/N mice, which express the X-linked immunodeficiency gene xid, are susceptible to Salmonella typhimurium. The basis for this susceptibility is currently unknown. However, previous studies (10) from this laboratory have provided evidence that susceptibility may be due to a defective anti-S. typhimurium antibody response. In that report we hypothesized that the defective antibody response may be a reflection of an altered S. typhimurium-specific B cell repertoire. In the studies described here, we have invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…However, a variety of studies have indicated a marked inability of xid mice to synthesize antibody to bacterial antigens, particularly polysaccharides (2,5,11). This in turn is associated with the inability of xid mice to develop immune resistance to infection with extracellular microorganisms (10,14,19). In normal mice, antibodies to polysaccharide antigens are preferentially produced within the IgM and IgG3 isotypes (21,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a variety of studies have indicated a marked inability of xid mice to synthesize antibody to bacterial antigens, particularly polysaccharides (2,5,11). This in turn is associated with the inability of xid mice to develop immune resistance to infection with extracellular microorganisms (10,14,19). In normal mice, antibodies to polysaccharide antigens are preferentially produced within the IgM and IgG3 isotypes (21,30).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports indicate reduced antibody production by these mice to systemically administered T-cell-independent antigens (2,17,29,30) and some T-cell-dependent antigens (5,23,24,28). Female mice that are homozygous or male mice that are hemizygous for xid have reduced resistance to systemic bacterial, protozoan, and viral infections linked to deficient antibody production (10,14,16,18,19). In this study, we compared mice expressing the xid gene with phenotypically normal mice to test our hypothesis that antibody is important for normal elimination of G. muris.…”
mentioning
confidence: 99%
“…The results presented here suggest that antibodies to the core polysaccharide region of the LPS molecule are not as important in the memory response to S. typhimurium infections as are anti-O antigen and anti-lipid A antibodies . Interestingly, recent studies from this laboratory suggest that salmonella-susceptible CBA/N mice which have been shown to be antibody defective (18), may have an altered repertoire to these determinants (66).…”
Section: Discussionmentioning
confidence: 99%
“…However, these mice are known to be extremely susceptible to certain bacterial infections (Duran and Metcalf, 1987).…”
Section: Husbandrymentioning
confidence: 99%